PRONUNCIATION PROFILING OF ENGLISH EDUCATION STUDY PROGRAMME STUDENTS: AN ANALYSIS OF SEGMENTAL SOUNDS AND WORD STRESS - Syahrul Jihad, - (2021)
This study investigates the students' pronunciation profile in producing the segmental and suprasegmental features in a scripted speech. This research involved fifteen of 4th semester English Department students who took Speaking in Academic Purposes 1 course. The methodology employed in this research was a qualitative research design. The data were collected through students speaking performance videos in Flipgrid by transcribing and converting the video into IPA transcriptions. The result of this research revealed that students have difficulty producing consonants, vowels, and diphthongs by substituting the targeted sound with similar sound; also, they replaced the word stress into a wrong syllable. This study expected to help both students and teachers to find a proper strategy in pronunciation instruction. Studying the student's pronunciation profile enables teachers to have a better understanding of the areas where students face the most difficult in delivering a speech. Keywords: Pronunciation, Segmental and suprasegmental features, Word stress.